The Nordic countries’ law on Sámi territorial rights - Allard, Christina (Arctic Review on Law and Politics, 2011)
Territorial rights are important for the Sámi people, as they are for all indigenous peoples. Land is the asset which supports the Sámi culture and responsible for its long-standing survival. This article compares property laws in Norway, Sweden and Finland as to how Sámi rights to land and natural resources are articulated and recognized. These rights are based on old doctrines: “immemorial usage” in Norway and “immemorial prescription” in Sweden and Finland. Although the doctrines are generally regarded as equivalent, the article discusses a few significant differences. Subsequently the basic principles underpinning the two doctrines are analysed, contrasted and discussed, with particular focus on reindeer herding rights.Keywords: Sámi rights, territorial rights, immemorial usage, immemorial pre- scription, Norwegian law, Swedish law, Finnish law, reindeer herdingCitation: Arctic Review on Law and Politics, vol. 3, 2/2011 p. 159–183. ISSN 1891-6252